2019
DOI: 10.1016/j.socscimed.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Re-engaging with places: Understanding bio-geo-graphical disruption and flow in adult brain injury survivors

Abstract: Acquired Brain Injury (ABI) is one of the most common causes of disability and death in adults worldwide. After a period of rehabilitation, many ABI survivors still face complex mind/body conditions when they try to take up their former life again. Besides lasting visible impairments such as weakness and loss of body balance, there are often less obvious disabilities such as extreme fatigue, hypersensitivity for stimuli, memory, concentration and attention problems or personality changes. The aim of this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
11
0
5
Order By: Relevance
“…We also cannot assume that there are certain places or activity domains that are attached to a certain combination of facilitating or hindering aspects, as all four domains were included in all the patterns of participation. Thus, in line with previous research [2,[24][25][26], to support people in their endeavour to maintain and recapture activities in places outside the home, it is important to understand that different aspects group together in different combinations to either facilitate or hinder participation.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…We also cannot assume that there are certain places or activity domains that are attached to a certain combination of facilitating or hindering aspects, as all four domains were included in all the patterns of participation. Thus, in line with previous research [2,[24][25][26], to support people in their endeavour to maintain and recapture activities in places outside the home, it is important to understand that different aspects group together in different combinations to either facilitate or hinder participation.…”
Section: Discussionmentioning
confidence: 72%
“…This can in part be related to the participants talking about familiar places and that people mostly engage in activities that they perceive as being a reasonable distance from their home. The location of home, in relation to the possibility of accessing other outside places, has also been emphasized in previous research [2,24]. Cutchin [28] suggested that meaning is created through the connection of person and place that is always in progress, that is, meaning is negotiated through changes in the relationship between person and place.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations